2013
DOI: 10.1016/j.rasd.2012.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Corpus callosum area in children and adults with autism

Abstract: Despite repeated findings of abnormal corpus callosum structure in autism, the developmental trajectories of corpus callosum growth in the disorder have not yet been reported. In this study, we examined corpus callosum size from a developmental perspective across a 30-year age range in a large cross-sectional sample of individuals with autism compared to a typically developing sample. Midsagittal corpus callosum area and the 7 Witelson subregions were examined in 68 males with autism (mean age 14.1 years; rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 76 publications
2
52
2
Order By: Relevance
“…Standardized scores of head circumference, brain volume, and other brain features have been routinely used to assess the distribution of brain characteristics in individuals with ASD (Barnea-Goraly et al, 2004, Courchesne et al, 2003, Herbert et al, 2004, Lainhart et al, 2006, Lainhart et al, 1997, Miles et al, 2000, Prigge et al, 2013), as well as other disorders, including mild traumatic brain injury (Kim et al, 2013, Lipton et al, 2012), bipolar disorder (Johnson et al, 2015), multiple sclerosis (Poonawalla et al, 2010), and Alzheimer's disease (Matsuda, 2014), among others. However, as it becomes commonplace to acquire multi-modal information from study participants, it becomes necessary to account for the multidimensional aspects of data.…”
Section: Discussionmentioning
confidence: 99%
“…Standardized scores of head circumference, brain volume, and other brain features have been routinely used to assess the distribution of brain characteristics in individuals with ASD (Barnea-Goraly et al, 2004, Courchesne et al, 2003, Herbert et al, 2004, Lainhart et al, 2006, Lainhart et al, 1997, Miles et al, 2000, Prigge et al, 2013), as well as other disorders, including mild traumatic brain injury (Kim et al, 2013, Lipton et al, 2012), bipolar disorder (Johnson et al, 2015), multiple sclerosis (Poonawalla et al, 2010), and Alzheimer's disease (Matsuda, 2014), among others. However, as it becomes commonplace to acquire multi-modal information from study participants, it becomes necessary to account for the multidimensional aspects of data.…”
Section: Discussionmentioning
confidence: 99%
“…For example, several studies have demonstrated neuroimaging abnormalities in ASD involving the structural and functional relations of several brain regions likely critical for VMI performance. These include the corpus callosum (Alexander et al, 2007; Prigge et al, 2013), frontal-parietal dysconnectivity (Just, Keller, Malave, Kana, & Varma, 2012), atypical white matter microstructure development (Cheng et al, 2010; Wolff et al, 2012), cerebellar connectivity (Mostofsky et al, 2009), medial prefrontal cortical abnormalities (Gilbert, Meuwese, Towgood, Frith, & Burgess, 2009) and a distributed specificity of cortical structural abnormalities including many of these implicated brain regions (Zielinski et al, 2012; Zielinski et al, 2014). Investigating these regions with multimodal neuroimaging methods may yield additional insights into why VMI ability appears to be attenuated in at least a subset of individuals with ASD and whether this may reflect differences in white matter microstructure and/or abnormalities within motor and perceptual networks.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Tissue loss in the CC has been associated with various types of cognitive decline and motor impairment such as Alzheimer's disease, 3 intellectual disability, 4 stroke, 1 traumatic brain injury, 5 multiple sclerosis, 6 temporal lobe and frontal lobe epilepsy, 7,8 deficient auditory language comprehension, 9 dyslexia, 10 Down syndrome, 11 Huntington disease, 12,13 and human immunodeficiency virus and/or AIDS. 14 Corpus callosal atrophy has also been linked to disorders such as schizophrenia, 15,16 Tourette syndrome, 17 bipolar disorder, 18,19 post-traumatic stress disorder, 20 autism, 21 obsessivecompulsive disorder, 22 and attention-deficit hyperactivity disorder. 23 Most studies on the CC in children have focused on autism and preterm children and adolescents.…”
Section: Introductionmentioning
confidence: 99%